ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI TINGKAT KEMISKINAN DI KABUPATEN LOMBOK TENGAH TAHUN 2016-2021 - Desy Yuliana; Muhamad Sayuti; Ahmad Suhendri (Jurnal Kompetitif : Media Informasi Ekonomi Pembangunan, Manajemen dan Akuntansi, 2023)
This research is entitled "ANALYSIS OF FACTORS AFFECTING POVERTY LEVEL IN LOMBOK CENTRAL DISTRICT 2016-2021". In this study, researchers wanted to see how inflation and education levels influence poverty as independent variables in Central Lombok Regency from 2016-2021. The type of this research is quantitative research with an associative approach. The analytical tool used in this study is multiple linear regression analysis. The results of this study are . The R-square value is 0.843 with a significance value (α) or alpha of 0.05 (5%). The R-square value in this study has the meaning that the influence of inflation and education level variables is able to explain the poverty variable of 84.3% %. That partially (each) the effect of the independent variable level of education on the dependent variable poverty in Central Lombok Regency is significant, this can be seen from the comparison value of T count which is greater than T table. As for the inflation variable, the effect is not significant in influencing poverty in Central Lombok Regency. While simultaneously (together) the influence of inflation and education level variables on poverty in Central Lombok Regency is significant. This can be seen from the comparison between the calculated F value and the F table, that the calculated F is greater than the F table value. Meanwhile, the variable that dominantly influences poverty in Central Lombok Regency is the independent variable of education level. This is evidenced by the coefficient value which is greater than the coefficient value of the inflation variable.